1973
DOI: 10.1007/bf00485540
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglucose isomerase gene duplication in the bony fishes: An evolutionary history

Abstract: Electrophoretic patterns of phosphoglucose isomerase (PGI) in bony fishes provide strong evidence for a model of genetic control by two independent structural gene loci, most likely resulting from a gene duplication. This model is confirmed by a comparison of certain kinetic and molecular properties of the PGI homodimers (PGI-1 and PGI-2) isolated from extracts of the teleost A s t y a n a x mexicanus. In addition, in most higher teleosts examined, the PGI enzymes show a regular pattern of tissue distribution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
2

Year Published

1974
1974
1998
1998

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(46 citation statements)
references
References 38 publications
4
40
0
2
Order By: Relevance
“…Notwithstanding a general flexibility in buffer requirements for some enzymes, we have found certain buffers particularly useful in a wide variety of fishes (see Avise and Selander, 1972;Avise and Kitto, 1973). Thus, we list the proteins examined in the bluegill with a generally appropriate buffer as follows: (1) esterases and general proteins-lithium hydroxide; (2) malate dehydrogenases, lactate dehydrogenases, glutamate oxalate transaminases, and isocitrate dehydrogenasescontinuous tris-citrate II; (3) phosphoglucose isomerases, phosphoglucomutases, lactate dehydrogenases, and indophenol oxidases-discontinuous tris-citrate (Poulik) (indophenol oxidase appears on gel slices stained for phosphoglucomutase when exposed to light); (4) isocitrate dehydrogenases and 6-phosphogluconate dehydrogenases-tris-malate.…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding a general flexibility in buffer requirements for some enzymes, we have found certain buffers particularly useful in a wide variety of fishes (see Avise and Selander, 1972;Avise and Kitto, 1973). Thus, we list the proteins examined in the bluegill with a generally appropriate buffer as follows: (1) esterases and general proteins-lithium hydroxide; (2) malate dehydrogenases, lactate dehydrogenases, glutamate oxalate transaminases, and isocitrate dehydrogenasescontinuous tris-citrate II; (3) phosphoglucose isomerases, phosphoglucomutases, lactate dehydrogenases, and indophenol oxidases-discontinuous tris-citrate (Poulik) (indophenol oxidase appears on gel slices stained for phosphoglucomutase when exposed to light); (4) isocitrate dehydrogenases and 6-phosphogluconate dehydrogenases-tris-malate.…”
Section: Methodsmentioning
confidence: 99%
“…And it is this factor that holds greater interest in relation to the evolutionary significance of genic variation in natural populations. The pattern of occurrence of unique alleles over loci in H. versicolor is as follows: Six of the nine alleles occur at loci that are polymorphic in both eastern and' western populations of H. chrysoscelis It has been suggested that, following gene duplication, one locus of the pair is free to accumulate new mutations and regulatory modifications because the other member maintains its original function and thus reduces the selective constraints normally imposed on a single gene-enzyme locus (Ohno, 1970;Avise and Kitto, 1973;Markert et al, 1975). This hypothesis predicts that, in the early stages of this process, duplicated loci will be more variable than unduplicated ones because new and initially deleterious mutations are shielded from the effects of selection.…”
Section: Genic Variability and Polyploidymentioning
confidence: 99%
“…Examples of such gene duplications have been documented in animals and plants (Ingran, 1961;Markert et a!., 1975;Avise and Kitto, 1973; Gottlieb, 1977;Pichersky and Gottlieb, 1983;Ellstrand eta!., 1983;Warwick and Gottlieb, 1985). The two loci coding for the cytosolic isozymes of PGI in D. serotinum have diverged structurally and must differ significantly in their sequences, because none of the electrophoretic variants at either locus overlap the mobility of any variant at the other.…”
Section: And Dcussionmentioning
confidence: 99%